2019
DOI: 10.1016/j.bbmt.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes of Allogeneic Transplantation for Primary Myelofibrosis among Hematopoietic Stem Cell Source Groups

Abstract: The choice of alternative donor is a major issue in allogeneic hematopoietic stem cell transplantation (HSCT) for patients with primary myelofibrosis (PMF) without an HLA-matched related donor. We conducted this retrospective study using the Japanese national registry data for 224 PMF patients to compare the outcomes of first allogeneic HSCT from HLA-matched related donor bone marrow (Rtd-BM), HLA-matched related donor peripheral blood stem cells (Rtd-PB), HLA-matched unrelated donor bone marrow (UR-BM), unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
2
16
0
1
Order By: Relevance
“…Takagi et al evaluated 14 UCB transplantation cases for myelofibrosis, including 11 secondary myelofibrosis from acute myeloid leukemia, and reported a 4-year OS of 29% ( 20 ). The recent nationwide retrospective study of HSCT for Japanese patients with primary myelofibrosis reported that the 1- and 4-year OS rates in UCB transplantation (n=29) were 48% and 27%, respectively, and that NRM was significantly higher in UCB transplantation than in HLA-matched related donor BM transplantation ( 21 ). Further analyses with more patients are required to evaluate the differences in the transplant outcomes for secondary myelofibrosis between UCB transplantation and related or unrelated donor transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Takagi et al evaluated 14 UCB transplantation cases for myelofibrosis, including 11 secondary myelofibrosis from acute myeloid leukemia, and reported a 4-year OS of 29% ( 20 ). The recent nationwide retrospective study of HSCT for Japanese patients with primary myelofibrosis reported that the 1- and 4-year OS rates in UCB transplantation (n=29) were 48% and 27%, respectively, and that NRM was significantly higher in UCB transplantation than in HLA-matched related donor BM transplantation ( 21 ). Further analyses with more patients are required to evaluate the differences in the transplant outcomes for secondary myelofibrosis between UCB transplantation and related or unrelated donor transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with MSD BM transplantation, the incidence of neutrophil and platelet recovery after unrelated UCB transplantation were significantly lower, and NRM at 1 year was higher (41% versus 16%, p = 0.046). 72 Therefore, careful management is required for patients who proceed to UCB AHSCT, especially in the early period.…”
Section: Stem Cell Sourcementioning
confidence: 99%
“…Raj et al reported on 56 MF patients transplanted between 2009 and 2015 from a family mismatched donor (i.e., relatives with ≥2 Ag HLA different from recipient), with a 2-year overall survival rate of 56% but a rather high non-relapse mortality (NRM) of 38% at 2 years [55]. In a recent retrospective review, NRM and 4-year OS rates were similar in patients receiving their first transplant from HLA-matched related donor peripheral blood stem cells or from HLA-MUD bone marrow, while long-term survival was inferior in patients transplanted from umbilical cord blood, partly due to higher NRM [56]. Information about haploidentical related donor in MF is still scarce; in a comparison between HLA-identical sibling and "alternative" donors, including 20 haploidentical, transplanted in the years 2011-2014, Bregante et al found similar survival rates in the two cohorts (72% and 69%, respectively) [57].…”
Section: Pretransplant Evaluation: Prognostic Scores and Consideratiomentioning
confidence: 99%